A Strategic Approach to Applying the Advanced Information System to Prevent Recurrence After Cholecystectomy - Seong-Ran Lee, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study was conducted to apply the advanced information system to prevent recurrence after cholecystectomy. The research was conducted on 102 people who visited general surgery clinics in C area from June 3 to August 27, 2019. The data were conducted with questionnaires and interviews. The general characteristics of the subjects were performed with Chi-square test. The comparison of symptoms according to the application of the advanced information system was analyzed for t-test. The results of this study are as follows. First, cholesterol levels decreased significantly after application than before application of advanced information system(t=3.91, p=.000). Second, physical fatigue decreased after 7 days of application than before information system application. Therefore, it has been confirmed that applying the advanced information system is effective in preventing recurrence after cholecystectomy.